Systematic review on routine monitoring of clinical outcomes in psychotherapy - Campodónico, Nicolás (2025)
This work proposes to carry out a systematic review on the routine monitoring of clinical results in psychotherapy. The systematic review selects 34 scientific articles that refer to publications in Spanish and English between 2024-2019. The main utility of MRR is that it allows the therapist to track changes during therapy and the feedback can improve the effectiveness of therapeutic interventions. Based on this, difficulties can be identified, abandonment or deterioration prevented, treatment adjusted to the needs and characteristics of each consultant, reinforced aspects that are being beneficial and, potentially, improve the therapeutic alliance. Additionally, MRR facilitates the evaluation of the effectiveness of psychological interventions in routine clinical practice, as well as the professional development and supervision of therapists. Therefore, it is concluded that monitoring in psychotherapy provides challenges, difficulties, but also benefits at different levels: therapeutic, technological and socioeconomic.